The effectiveness of internal rhythm in the poetry of Ridicule with Ibin Bassam al-Bagdadi (Journal of the College of Education for Women, 2019)
This study seeks to uncover the aesthetics of the internal rhythm and its effectiveness inenriching the poetic text with the music tone at represented in the art of repetition and thepermit and recycling division and put back on the chest and the naturalization interview andcounterpoint.And try to stand on the impact of internal rhythm to highlight the meaning of spelling andirony with poet Ibn Bassam Al-Bagdadi and have a close look at the literary andpsychological motivations that led the poet to employ these colors in his ridicule and theextent of its contribution to intensify the poetic alphabetic flush.And deepening the meanings and provide poetic text in different aesthetics, there is no doubtthat the old and modern Arabic poem and has focused to install its internal rhythm and justifyreclining on it as phonetic stand to feel hearing with harmony and compatibility andacceptance.